2005
DOI: 10.1029/2004jd005018
|View full text |Cite
|
Sign up to set email alerts
|

Polar vortex evolution during the 2002 Antarctic major warming as observed by the Odin satellite

Abstract: In September 2002 the Antarctic polar vortex split in two under the influence of a sudden warming. During this event, the Odin satellite was able to measure both ozone (O3) and chlorine monoxide (ClO), a key constituent responsible for the so-called “ozone hole”, together with nitrous oxide (N2O), a dynamical tracer, and nitric acid (HNO3) and nitrogen dioxide (NO2), tracers of denitrification. The submillimeter radiometer (SMR) microwave instrument and the Optical Spectrograph and Infrared Imager System (OSIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 40 publications
4
41
0
1
Order By: Relevance
“…The single profile precision (total error) in the lower stratosphere is estimated at 19-31% (29-36%) at an altitude resolution of 4 km. ClO mixing ratios measured by MIPAS before 20 September and from 25 September onwards are in agreement with measurements by the Submillimeter Radiometer (SMR) on the Odin satellite (Ricaud et al, 2005). Unfortunately, no SMR measurements have been published for the 22-24 September period.…”
Section: Mipas Measurementssupporting
confidence: 79%
“…The single profile precision (total error) in the lower stratosphere is estimated at 19-31% (29-36%) at an altitude resolution of 4 km. ClO mixing ratios measured by MIPAS before 20 September and from 25 September onwards are in agreement with measurements by the Submillimeter Radiometer (SMR) on the Odin satellite (Ricaud et al, 2005). Unfortunately, no SMR measurements have been published for the 22-24 September period.…”
Section: Mipas Measurementssupporting
confidence: 79%
“…Ricaud et al, 2005). A next step of our work is to make comparisons at a global scale and for long time series using satellite data such as those of ODIN and ENVISAT.…”
Section: Resultsmentioning
confidence: 99%
“…Lefèvre et al, 1998;Wetzel et al, 2002;Stowasser et al, 2003;Ricaud et al, 2005) mid-latitudes during summer time are overestimated by the KASIMA model below 30 km . Comparisons between Reprobus and the Odin satellite measurements have shown that the model overestimated the N 2 O amounts observed by Odin/SMR at mid-latitudes in mid-September 2002 (Ricaud et al, 2005). Similar disagreements are observed with preliminary measurements of the MIPAS instrument on board the ENVISAT satellite for the same period (R. Runhke, personal communication).…”
Section: Model Calculationsmentioning
confidence: 90%
See 2 more Smart Citations